Correction: Donnelly et al. A Case of DNAJC12-Deficient Hyperphenylalaninemia Detected on Newborn Screening: Clinical Outcomes from Early Detection. Int. J. Neonatal Screen. 2024, 10, 7 - Colleen Donnelly; Lissette Estrella; Ilona Ginevic; Jaya Ganesh (International Journal of Neonatal Screening)
In the original publication [...]